Will China Be a Responsible Great Power? - Ho, Benjamin (2018)
The changes made to the CCP constitution to allow President Xi Jinping an indefinite stay of power have led to concerns about Beijing’s long-term geopolitical gameplan. At the same time, with great power comes great responsibility. What China does in the region will be closely watched.